Gu-Ben-Fang-Xiao Decoction Ameliorated Murine Asthma in Remission Stage by Modulating Microbiota-Acetate-Tregs Axis - Dong, Yingmei; Yan, Hua; Zhao, Xia; Lin, Rui; Lin, Lili; Ding, Yuanyuan; Liu, Liwei; Ren, Lishun; Xing, Qiongqiong; Ji, Jianjian (Frontiers in Pharmacology, 2020)
Dysbiosis of gut microbiota is a critical factor in the pathogenesis of asthma. Manipulating gut microbiota is a promising therapeutic intervention in asthma, and is being extensively studied. Gu-Ben-Fang-Xiao Decoction (GBFXD), derived from traditional Chinese medicine, is an effective and safe therapeutic formula for asthma in remission stage (ARS). Herein, we showed that GBFXD treatment remarkably alleviated ARS by improving respiratory function and lung histopathology. Asthmatic mice displayed a dysbiosis of gut microbiota, represented by significantly increased abundance of Bacteroidetes and decreased abundance of Firmicutes in gut, while GBFXD treatment reversed the gut dysbiosis in asthmatic mice at phylum, family and genus level. Moreover, our data showed GBFXD treatment increased the abundance of SCFAs-producing bacteria in asthmatic mice, such as Firmicutes, Lachnospiraceae and Bifidobacteriaceae, which consequently led to elevated levels of SCFAs. Furthermore, GBFXD treatment significantly enhanced regulatory T cell differentiation via SCFAs, particularly acetate, in asthmatic mice. More critically, the protective effect of GBFXD was shown to be transmissible among asthmatic mice through co-housing microbiota transplantation. Antibiotic cocktail and acetate replenishment experiments also further substantiated the importance of SCFA-producing gut microbiota in GBFXD action. We thus demonstrated for the first time that gut microbiota dysbiosis existed in ARS. GBFXD could ameliorate ARS through the microbiota-acetate-Tregs axis.